Assessment of Health Status of the Elderly and Pre-elderly at a Malaysia Elderly Care Centre - Bani, Nurul Aini; Hassan, Mohamad Zaki; Mad Kaidi, Hazilah; Mohd Hashim, Nor Fazilah; Dziyauddin, Rudzidatul Akmam; Musa, Rafizah; Suhot, Mohamed Azlan; Usman, Sahnius; Muhammad-Sukki, Firdaus; Abu-Bakar, Siti Hawa; Mas'ud, Abdullahi Abubakar (International Journal of Integrated Engineering, 2018)
They were once called the baby boomers, born between 1946 to 1964, but now aged above 50 years old, they contribute to the increasing number of elderly population in Malaysia. Age classification for elderly people varies between countries but commonly pre-elderly people is defined as those aged between 50 to 64 years old while those aged more than 64 years old fall in elderly category. In Malaysia, it is projected that the elderly population will make up for 10% of the total population or 3.4 million by year 2020. Without effective and comprehensive healthcare system, the healthy lifestyle of this elderly population can be affected thus prohibiting them to return to their premorbid function. In this study, the health status of pre-elderly and elderly community residing at an Elderly Care Center in Selangor, Malaysia is assessed. In overall, 12 male occupants (4 elderly and 8 pre-elderly people) aged 50 years and above were interviewed to obtain data on their sociodemographic characteristics, medical history, hand functionality and hand strength measurements. The overall sample mean (standard deviation) age are 63 (8) years. The mean (standard deviation) for BMI is 20.26 (2.73) kg/m2 that falls in the normal category despite the visible nutritional deficiencies sign and symptoms on their physical body and facial. The mean (standard deviation) of handgrip measurements is 12.47 (6.69) kg, which is quite low but reasonable due to ageing factor.